Um estudo bíblico-teológico sobre o “Trono” em Ap 4: uma ênfase nas palavras θρόνος e καθήμενος - Brito, Marcos Paiva (2018)
Apocalypse 4 is a simple reading text in portuguese, but not so simple in the language in which it was written (Greek). At first glance, the portuguese language presents no difference from the throne of verse 2 to the thrones of verse 4. The word (καθήμενος) closest to the term in verse 2 also appears in verse 4. In the first, the seer sees One sitting in the throne. Ιn the second, he sees twenty-four elders seated on twenty-four thrones. These elders are apparently seated on these thrones as the One sitting on the throne in verse 2. However, the greek text presented a variation in the lexical analysis of the term in the two verses. The purpose of this study was to conduct a biblical-theological study of the throne in Revelation4, considering the grammatical analysis of the noun θρόνος and the main words attached to it. From a critical-textual study, from the translation of the segmented pericope, and from the morphological and syntactic analyzes of the term in Revelation 4, the primary meaning of the term was defined. The secondary sense of it was also considered in accordance with the Greek case in which it is ruled. This bible study is based on the Fourth Edition of the Greek New Testament. From it is abstracted the text of Revelation 4, which is segmented and translated literally. To analyze the text lexically, Greek dictionaries, lexicons, concordances, biblical keys and Greek grammars were consulted. In the exegesis part of the text, comments from scholars in the book of Revelation were searched. The morphosyntactic analysis counted current greek grammars. The passage from Revelation 4, concerning the throne of God and the other thrones present in the text and in the book, is simple but presents lexically considerable differences. Some scholars consider the thrones of the twenty-four elders lesser than the throne of God. Others consider these thrones equal to the throne of God. However, grammatical study has shown that God's throne differs from the thrones of the elders. And his presence in the book of Revelation brings with it unparalleled characteristics of God and His throne, which others possess as a reflection of these characteristics